Sociocultural trail within the dialogical self: I-positions, institutions, and cultural armory. (March 2017) - Gube, Jan
This paper discusses the interface of dialogical self-theory and institutional context with reference to the schooling of ethnic minorities. It proposes a more nuanced approach to identifying cultural resources within institutions that contribute to dialogical movements and positioning, thereby advancing the application of dialogical self-theory within institutionalized spaces. Drawing on sociocultural concepts of identity construction, the discussion outlines how I-positions are tethered to social practices, relationships, power, and relations within institutions. These cultural resources are highlighted because they foreground how dialogical tensions occur and transcend opposing voices within an institution itself. In providing a textual analysis of Edward Said's encounter with a school rule that tended to suppress his Arab identity, the integrated dialogical self-theory and sociocultural approach can highlight the contours of dialogical frictions as a result of negotiation with power across an institution to arrive at a desired I-position.